A review of potential factors contributing to epidemic cholera in Yemen - Al-Gheethi, Adel; Noman, Efaq; David, Bala Jeremiah; Mohamed, Radin; Abdullah, Abd. Halid; Nagapan, Sasitharan; Mohd, Amir Hashim (IWA Publishing, 2018)
The menace of cholera epidemic occurrence in Yemen was reported in early 2017. Recent reports revealed that an estimated 500,000 people are infected with cholera whereas 2,000 deaths have been reported in Yemen. Cholera is transmitted through contaminated water and food. Yemen is the least developed country among the Middle East countries in terms of wastewater and solid waste management. The population of Yemen is about 24.5 million and generates about 70–100 million m3 of sewage. An estimated 7% of the population has sewerage systems. It has been revealed that 31.2 million m3 of untreated sewage is used for irrigation purposes especially for vegetables and Khat trees. In addition, more than 70% of the population in Yemen has no potable water. They depend on water wells as a water source which are located close to sewage disposal sites. The present review focuses on the current status of water, wastewater as well as solid waste management in Yemen and their roles in the outbreak of cholera. Future prospects for waste management have been proposed.